A Analisis Kerentanan Psikososial Residivis Tindak Pidana Peredaran Gelap Narkotika: Suatu Identifikasi Atas Faktor-Faktor Pencetus Pelanggarannya - Miardi Miardi; Arthur Josias Simon Runturambi; Ahmad Ibrahim Badri (Humanitas (Jurnal Psikologi), 2024)
The recidivism rate in Indonesia in 2023 reached 3.55%. On the other hand, the highest number of residents of correctional institutions comes from narcotics crimes, which amounted to 52.97% or 135,823 people. In the case of drug crimes, former defendants in drug crimes often commit repeated crimes due to many factors, including psychosocial aspects. This study focuses on the factors that trigger drug trafficking recidivism through psychosocial vulnerability analysis. We found several factors that triggered recidivism, such as drug protection, drug-prone areas and family, which then triggered the informants' recidivism. Using a qualitative methodology with case study method, the research found a vulnerability of the psychosocial aspects of the informants with drug crime, which is an organized crime. This research provides new information on how ex-drivers are involved in recidivism which can later be useful as material in the intervention module for interventions for ex-drivers in the re-entry process involving the social environment, family based on psychosocial needs.